Innovative Multiple Matching Charts approach to support the conceptual design of hypersonic vehicles. (September 2020) - Ferretto, Davide; Fusaro, Roberta; Viola, Nicole
Several well-established best practices and reliable tools have been developed along the years to support aircraft conceptual and preliminary design. In this context, one of the most widely used tool is the Matching Chart (MC), a graphical representation of the different performance requirements (curves representing the thrust-to-weight ratio (T/W) requirement as function of the wing loading (W/S)) for each mission phase. The exploitation of this tool allows the identification of a feasible design space as well as the definition of a reference vehicle configuration in terms of maximum thrust, maximum take-off weight, and wing surface since the very beginning of the design process. Although the tool was originally developed for conventional aircraft, several extensions and updates of the mathematical models have been proposed over the years to widen its application to innovative configurations. Following this trend, this paper presents a further evolution of the MC model to support the conceptual design of high-speed transportation systems, encompassing supersonic and hypersonic flight vehicles. At this purpose, this paper reports and discusses the updates of the methodology laying behind the generation of the MC for high-speed transportation. Eventually, the results of the validation of the updated methodology and tool are reported, using as case study, the STRATOFLY MR3 vehicle configuration, a Mach 8 antipodal civil transportation system, currently under development within the H2020 STRATOFLY project.